Rituximab with prednisolone as first‐line treatment in pemphigus vulgaris. (1st May 2020) - Scorer, M.; Setterfield, J.F.; Harman, K.E.
Abstract: Linked Article: Chen et al . Br J Dermatol 2020; 182 :1111–1119 .